Catheter-directed thrombolytic therapy for lowerextremity deep vein thrombosis: a case report: Lokalna katetrska tromboliza kot terapija za globoko vensko trombozo – poročilo o primeru. - Pajnik Snoj, Aja; Markota, Andrej (Acta Medico-Biotechnica, 2022)
Patients with lower-extremity deep vein thrombosis commonly present to emergency departments. However, the propagation of deep vein thrombosis to phlegmasia cerulea dolens is rarely seen. Catheter-directed thrombolytic therapy is widely accepted as an appropriate treatment for severe forms of lower-limb deep vein thrombosis such as phlegmasia cerulea dolens. It is usually available only in a few selective hospitals. This study aimed to present a case of the first such procedure performed in the University Medical Centre Maribor.
Keywords: catheter-directed thrombolysis; deep vein thrombosis; percutaneous interventional treatment; phlegmasia cerulea dolens